Indonesian postgraduate students’ intercultural communication experiences in the United Kingdom - Sarah Aisha; Deddy Mulyana (Jurnal Kajian Komunikasi, 2019)
Despite the increasing number of Indonesian postgraduate students studying overseas, including in the United Kingdom, not many studies have been done on their intercultural communication experiences and academic engagement. This research aims to investigate Indonesian postgraduate students’ intercultural communication experiences and academic engagement in the United Kingdom. In this study, we address the following research question: What are the hindering factors and the facilitating factors of Indonesian postgraduate students’ academic engagement within their courses of study? A qualitative research method is used in this study, based on semi-structured interviews with 13 participants. The results of the study indicate that the students are more engaged in some areas, such applying deep learning strategies by connecting ideas, and less engaged in others, such as interacting with academic staff. Several interrelated factors were indicated as contributing to facilitating or hindering academic engagement which include sociocultural, institutional, and individual factors. The hindering factors consists of the transition to a new academic environment, intense academic workload, ‘expert’ or ‘boring tutors, linguistic barriers, and having feelings of uneasiness. Conversely, the facilitating factors consist of institutional support service, course design, caring and casual tutors, learning from prior experiences, having the initiative to ask, and realizing to make the most of the opportunity.